Prompting and Fine-tuning Pre-trained Generative Language Models - Moreira, Johny; da Silva, Altigran; Barbosa, Luciano (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2023)
There has been an explosion of available pre-trained and fine-tuned Generative Language Models (LM). They vary in the number of parameters, architecture, training strategy, and training set size. Aligned with it, alternative strategies exist to exploit these models, such as Fine-tuning and Prompt Engineering. However, many questions may arise throughout this process: Which model to apply for a given task? Which strategies to use? Will Prompt Engineering solve all tasks? What are the computational and financial costs involved? This tutorial will introduce and explore typical modern LM architectures with a hands-on approach to the available strategies.